Iterative approach to enantiopure syn/anti-1,3-polyols via proline-catalyzed sequential alpha-aminoxylation and horner-wadsworth-emmons olefination of aldehydes - Kondekar, Nagendra B.; Kumar, Pradeep (Organic Letters, 2009)
Iterative use of proline-catalyzed tandem alpha-aminoxylation and HWE olefination of aldehydes provided a simple access to 1,3-polyols. The feasibility of this approach is initially studied to synthesize syn- and anti-1,3-diols and is further extended to a syn/syn-1,3,5-triol at a useful level of asymmetric induction and yield. Its usage is Illustrated by the short synthesis of a hydroxylactone pheromone component, (2S,3S)-2-hydroxyhexylcyclopentanone.

Enantioselective synthesis of syn/anti-1,3-amino alcohols via proline-catalyzed sequential alpha-aminoxylation/alpha-amination and horner-wadsworth-emmons olefination of aldehydes - Jha, Vishwajeet; Kondekar, Nagendra B.; Kumar, Pradeep (Organic Letters, 2010)
A novel and general method for asymmetric synthesis of both syn/anti-1,3-amino alcohols is described. The method uses proline-catalyzed sequential alpha-aminoxylation/alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step. By using this method, a short synthesis of a bioactive molecule, (R)-1-((S)-1-methylpyrrolidin-2-yl)-5-phenylpentan-2-ol, is also accomplished.

Synthesis of (R)-coniine and (S)-coinicine via organocatalytic alpha-aminoxylation of an aldehyde - Kondekar, Nagendra B.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A short and efficient synthesis of the indolizidine alkaloid (S)-coinicine has been achieved using organocatalytic sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of an aldehyde catalyzed by L-proline. Similarly, a common organocatalytic alpha-aminoxylation route has been developed for the asymmetric synthesis of both (R)-coniine and (S)-coinicine.
Keywords: hemlock alkaloids; organocatalysis; Proline; sequential reactions; synthesis

Synthesis of (R)-selegiline via hydrolytic kinetic resolution - Kondekar, Nagendra B.; Kumar, Pradeep (Synthetic Communications, 2011)
[image omitted] A short and enantioselective formal synthesis of (R)-selegiline has been achieved using Jacobsen's hydrolytic kinetic resolution (HKR) of phenyl propylene oxide.
Keywords: Cobalt-based chiral salen complex; Hydrolytic kinetic resolution; MAO inhibitors; phenyl propylene oxide; selegiline